Dalam Bayang-bayang Maskulinitas: Studi Kasus Branding Politik Prabowo Subianto - Wahyu Triyogo Asbari; Edi Suwiknyo Suwiknyo; Eddi Kurnianto Saptawan Saptawan; M. Zacky Al Hosen Hosen (Jurnal Komunikasi Profesional, 2023)
Prabowo will run again as a presidential candidate in the 2024 presidential election. However, the 2024 presidential election is different from the previous elections. So far, Prabowo often uses visual displays that emphasize masculinity, such as firmness, courage and courage. It turned out that Prabowo lost. In 2019, the support team tried to change Prabowo's image by launching a rebranding with the slogan "The New Prabowo". In fact, Prabowo's campaign still seems to carry various symbols of masculinity, and once again ends with a defeat by Jokowi. This article tries to see what kind of rebranding the Prabowo support team is planning, what are the obstacles and challenges in shaping their candidate. This article is complemented by an interview with one of Prabowo's spokespersons, namely Dahnil Azhar Simanjuntak. At the end there are also pointers regarding Prabowo's latest election strategy, indicating a change from previous strategies. It is hoped that this article can provide an overview of the implementation of Prabowo's campaign at that time, and provide additional knowledge for readers. Abstraksi : Prabowo akan maju kembali sebagai calon presiden pada Pilpres 2024. Namun Pilpres 2024 berbeda Pemilu sebelumnya. Selama ini Prabowo sering menggunakan tampilan visual yang menonjolkan sisi maskulinitas seperti ketegasan, kegagahan dan keberanian. Ternyata Prabowo kalah. Pada 2019, tim pendukung mencoba mengubah citra Prabowo dengan meluncurkan rebranding dengan slogan “The New Prabowo”. Kenyataannya kampanye Prabowo masih terlihat mengusung berbagai simbol maskulinitas, dan sekali lagi diakhiri dengan kekalahan dari Jokowi. Artikel ini mencoba melihat seperti apa rebranding yang direncanakan tim pendukung Prabowo, apa yang menjadi kendala dan tantangan dalam membentuk kandidat mereka. Artikel ini dilengkapi dengan wawancara salah satu jueu bicara Prabowo, yaitu Dahnil Azhar Simanjuntak. Di bagian akhir juga ada pointers mengenai strategi pemilu Prabowo yang terbaru, menunjukkan adanya perubahan dari strategi-strategi sebelumnya. Diharapkan artikel ini bisa memberikan gambaran mengenai pelaksanaan kampanye Prabowo saat itu, dan memberikan tambahan pengetahuan bagi pembacanya.